Reducing uncertainty in source area exploration of mineralized glacial erratics using terrestrial cosmogenic radionuclide dating - Peltonen, Veikko; Kultti, Seija; Putkinen, Niko; Rinterknecht, V.R.; Hall, Adrian; Whipp, David (Journal of Geochemical Exploration, 2024)
International audience Mineral exploration often relies on sedimentary indicators as first signs of a potential nearby mineralization in bedrock. The transportation of sediment by glacial and fluvial processes introduces uncertainty into the tracing of potential source areas of the sediment. This is particularly challenging in areas where glacial erosion has been weak, resulting in reworking of sediments and multiple directions of transportation. In this study we explore the use of Terrestrial Cosmogenic Nuclides (TCN) alongside conventional mineral exploration methods to better link indicators with their potential source areas. The study focuses on a mineral exploration project site in northern Finland in a region with stratigraphic evidence of multiple glaciations. The project targets the source of discovered Au mineralized erratic boulders that have been deposited atop the most recent till unit. The superposition suggests transportation in the latest glacial event. However, the 10 Be (35.9 +/- 1.3 and 30.3 +/- 1.1 ka) and 26 Al TCN ages analyzed from the mineralized erratics precede the latest glacial event, suggesting the possibility of multiple stages of transportation. The local bedrock TCN inventories (48.9 +/- 1.9 and 85.3 +/- 2.8 ka) are well preserved, suggestive of weak glacial erosion and therefore short recent transportation distances for the mineralized erratics. By combining the TCN interpretation and historical ice flow directions derived from the till stratigraphy, we suggest a nearby source locating NNW of the dated erratics. We find that TCN dating can limit some of the transportation related uncertainties in glaciated terrain. Through the analysis of TCN inventories from bedrock and boulders it is possible to characterize glacial erosion and boulder transportation, and to identify repeated exposure events, i.e., the possibility of multi -staged transportation. The method benefits from combined use of stratigraphic investigations that can identify both the local transportation directions and ...